Estimation of transport accessibility in case of rational transport hub location - Rossolov, Alexander; Naumov, Vitalii; Popova, Nadezhda; Vakulenko, Ekaterina; Levchenko, Olena (Transport, 2021)
The public transit accessibility has become an important attribute of social and economic activity of contemporary society. The shift to the sustainable paradigm of the current cities’ development has made public transport the basic mean for population travels execution. The spatial character of the travels in the megapolises supposes its implementation with the transfers. This may result in the travel time increase if the transport hubs are designed or located inefficiently. In some cases, the transport hub locations do not reflect the current demand for public transport services and require the fulfilment of the infrastructure measures. The paper presents the Hub Location Problem (HLP) solving in the case of rapid transit and trolleybus lines interaction. It has been proposed the combined criterion for the HLP solving based on the two-dimensional coordinate system with the estimation of passenger walk turnover. The simulation procedure to estimate the transport hub relocation has been made in the PTV VISUM software in the case of the Industrial District of Kharkiv City (Ukraine). The results of the economic effect available from the transport hub rational location have been estimated.